Aortoesophageal Fistula after Thoracic Endovascular Aortic Repair for Blunt Thoracic Aortic Injury - Masakazu Nitta; Taro Tamakawa; Natsuo Kamimura; Tadayuki Honda; Hiroshi Endoh (Journal of Trauma and Injury)
Although thoracic endovascular aortic repair (TEVAR) has grown to become the standard of care to treat blunt thoracic aortic injury (BTAI), the long-term effects of TEVAR are still unclear. We here present a 72-year-old man with BTAI due to a traffic accident. He successfully underwent TEVAR and was transferred to another rehabilitation hospital 2 months after the accident. However, 1 month later, he underwent gastroscopy with fever and hematemesis and was diagnosed with aorto-esophageal fistula (AEF). After being re-transferred to Niigata University Medical and Dental Hospital, we tried to convince him to undergo surgical treatment, but he strongly refused. He received palliative care and died due to rupture of the aortic pseudoaneurysm 3 days after the hospital transfer. Fatal complications like AEF may occur after TEVAR, so clinicians need to carefully follow patients who underwent TEVAR.